144k views
0 votes
Solve the system of equations by the addition method 3x - 2y = 78x + 6y = 13

User Naomi K
by
5.6k points

1 Answer

7 votes

In order to solve the system using the addition method, we can add three times the first equation to the second equation (this way we can cancel -6y with 6y), so we have that:


\begin{gathered} 3\cdot(3x-2y)+8x+6y=3\cdot7+13 \\ 9x-6y+8x+6y=21+13 \\ 17x=34 \\ x=(34)/(17)=2 \\ \\ 3x-2y=7 \\ 3\cdot2-2y=7 \\ 6-2y=7 \\ -2y=7-6 \\ -2y=1 \\ y=-(1)/(2) \end{gathered}

So we have that x = 2 and y = -1/2

User Eljiwo
by
5.7k points